The role of sport for youth amidst trauma and chaos. Issue 5 (19th October 2016) - Massey, William V.; Whitley, Meredith A.
Abstract: Sport remains a huge draw for young people, with the dominant narrative remaining one of sport for good. However, it is likely that alternative narratives exist, particularly as the role of sport in development is complex and multi-faceted. Moreover, within the dominant narrative that proposes the use of sport for positive development, how sport contributes to developmental outcomes over time, and what impact sport has on various life domains remains an area of interest for scholars and practitioners alike. Given this, and in response to concerns about positivist and post-positivistic paradigms, a narrative analysis was conducted to examine the role of sport in the lives of former athletes who experienced multiple traumas and/or adverse experiences in their childhood. Utilising a constructionist philosophical orientation, in-depth individual interviews were conducted with 10 former athletes who achieved a high level of success in sport, attended college, and have self-reported to be living a healthy and/or fulfilling life. Results of a structural and content analysis are reported in which, following entry into sport, three narratives were shared: (1) sport as a developmental asset, (2) sport as a place of celebrated deviance, and (3) sport as a neutral influence amongst complex systematic factors. While all participants discussed the role of sport in their lives, positive and negative outcomes were dependent on the structure provided, relationships developed, and opportunities provided through the sport experience. Continued theory development examining the systematic influences that shape youth development and behaviour over time is needed for sport professionals.